Sonalgaz دور القيادة التحويلية في ترقية أداء المورد البشري دراسة حالة بمديرية توزيع الكهرباء والغاز بالأغواط - بن واعر محمد الأمين; رحماني يوسف زكرياء (جامعة عمار ثليجي الاغواط, 2022)
The study aimed to identify the impact of transformational leadership on the performance of workers in the Electricity and Gas Distribution Corporation and the Laghouat Unit, and the SPSS statistical program was used to analyze the questionnaire data. The first, while the second hypothesis was positive, meaning that the intellectual consultation had a role for the intellectual advice (creative encouragement) in upgrading the performance of the human resource, then the third hypothesis was completely positive through the presence of individual considerations in the promotion of the human resource among the workers of the Electricity and Gas Distribution Company, Laghouat branch, while The fourth hypothesis was also positive, which showed that motivation has a role in upgrading the human resource in the Electricity and Gas Distribution Corporation, Laghouat Branch.